REVIEW ELECTRONIC COMMERCE UNTUK MEMPERLUAS JARINGAN PEMASARAN - Sidiq, Ahmad (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
To day, For the part of corporation, e-commerce bot merely buy and sell product according to online, on the contrary, e-commerce cover entire process from developments, marketing, sale, delivery, service, and payment to various product and service, buy in base global network customers, with support from network business partners throughout world. in this article be discussed about sisitem e-comerce will base on internet resource and many another information technology to support every step from this process. first identifies various principal category and trend in ecommerce, second identify various important process from system e-commerce. third, identify primary factor and rules that wanted web store so that success in e-commerce. identify and explanation business value from several market kinds e-commerce. latest discuss various benefit and surplus with weakness from several alternatifcliks and brick in e-commerce, in marketing network extension